Sudoko Bee solving and generating Sudoku puzzles using improved Artificial Bee Colony - Pacurib, Jaysonne A.; Seno, Glaiza Mae M. (Jaysonne A. Pacurib [and] Glaiza Mae M. Seno, 2009)
Sudoku puzzles belong to a set of hard problems called NP-Complete problems. Several algorithms have been tried to solve these puzzles including backtracking and other deterministic algorithms. These approaches were effective in solving easy puzzles; however, they have been proven to be inefficient when dealing with harder Sudoku. Recent developments in the field of Computer Science have shifted focus from deterministic algorithms to non-deterministic algorithms. More specifically, they have turned their attention to nature. In 2005, a new algorithm called Artificial Bee Colony Algorithm has been developed and has been successfully applied to a wide array of NP-Complete problems. This algorithm mimics the way bees forage for food. This paper explores the possibility of using Artificial Bee Colony in solving and generating Sudoku Puzzles. ABC was used to solve 6x6, 9x9 and 12x12 Sudoku Puzzles of varying difficulty. The algorithm was able to solve all the puzzles with 100% accuracy. The results obtained support the conclusion that ABC can be used to solve Sudoku Puzzles.